The Presentation Form and Function of Gondang Uning-uningan by the Sabas Group in the Traditional Batak Toba Wedding Ceremony in Jambi - Rian Naftanael Gultom (Repertoar, 2026)
This study aims to describe the presentation and function of Gondang Uning-uningan Grup Sabas in traditional Batak Toba wedding ceremonies in Jambi. This study uses a descriptive qualitative method. Data collection techniques include observation, interviews, documentation, and literature study. The compilation process begins with the first stage of data reduction, followed by data presentation and conclusion drawing. The analysis found elements of presentation in the traditional Batak Toba wedding ceremony in Jambi that are incorporated into the ceremony, including the presentation, number of musicians, performance time, number of songs, and performance venue. In the presentation of Gondang uning-uningan, the songs performed are correlated with the wedding party. These include the procession of making tua ni gondang (gondang mula mula), the presentation of tintin marangkup (tintin marangkup), the presentation of ulos (ulos passamot), kasihnya seperti sungai, emeni simbolon), and paulak une (gondang hasahatan and si tio-tio). Seven functions of the Sabas Group's Gondang uning-uningan in Batak Toba traditional wedding ceremonies were found, including emotional expression, aesthetic appreciation, entertainment, communication, symbolism, physical response, and social norms.